Milton's good God a study in literary theodicy - Danielson, Dennis Richard 1949- (Cambridge University Press, 1982)
Few writers have achieved the synthesis of art and idea that was attained by John Milton in Paradise Lost. In that work the poet addressed one of the most important questions in philosophy and religion: How could God, if he is omnipotent and wholly good, have made a world in which there is so much evil? In this book Professor Danielson examines Paradise Lost, focusing on Milton's treatment of creation, chaos, predestination, free will, God's foreknowledge, the Fall of Man and the nature of human existence before the Fall. The author thereby not only lays a systematic foundation for understanding Milton's defence of the creator's justice and goodness but also explores how the literary character of that defence gives it a unique human vitality, dramatic consistency and logical coherence. Milton's Good God is an interdisciplinary study, which will lead the student of literature to a deeper appreciation of Paradise Lost while drawing the student of ideas to a fuller awareness of the importance of Milton's work for the fields of philosophy, theology and intellectual history
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Milton, John / 1608-1674 / Paradise lost; Milton, John / 1608-1674 / Religion; Milton, John -- 1608-1674 -- Paradise lost; Good and evil in literature; Fall of man in literature; Theodicy in literature; God in literature; Theodizee; Hochschulschrift